Optimasi Penggunaan Faktor Eksposi Pemeriksaan Ossa Manus dengan Kualitas Citra Objektif dan Subjektif - Irsal, Muhammad; Alfajri, Muhammad Rival; Ananta, Vincentius Deva; Anwar, Khairil; Sriyatun, Sriyatun (Poltekkes Kemenkes Tanjung Karang, 2021)
In producing a good radiographic image, an optimization method is needed. This study was conducted to seek optimization of the radiographic examination of the manus ossa with objective and subjective image quality analysis. The research method is quantitative experimental, using a variety of exposure factors: 40kV 4 mAs, 40kV 10 mAs, 46 kV 5 mAs, 53 kV 2,5 mAs, 61kV 1,25 mAs. Then an objective quality analysis is carried out by measuring the pixels value, Signal to Noise Ratio (SNR), and the Exposure Index (EI) value as an indicator of exposure. For subjective image analysis with the assessment of image anatomy criteria using the method Visual Grading Analysis (VGA), then the test was carried out Wilcoxon to determine the relationship of respondents to VGA assessment. The results of the study obtained that the optimization method of the examination manus ossa at the exposure factor of 46 kV 5 mAs with the results of an objective image quality analysis of the range of pixel valueÂ 183,7 - 3, the SNR range of 12,2-1,77 while the subjective image quality analysis of the results VGA all images on a variety of exposure factors can be used in establishing a diagnosis. For the exposure indicator with the lowest EI at an exposure factor of 46 kV 5 mAs. The results of the Wilcoxon p-value>0,05 so that there was no difference in the VGA value by 2 radiographers, therefore all image results on variations in exposure factors could be used in the radiographic examination of the ossa manus.